EVALUASI KABIJAKAN PROMOSI JABATAN DI BADAN KEPEGAWAIAN PENDIDIKAN DAN PELATIHAN DAERAH KABUPATEN MANGGARAI BARAT PROVINSI NUSA TENGGARA TIMUR - Nur, Sunardy; Burhanuddin, Burhanuddin; Sudarmi, Sudarmi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACTThis study used qualitative research with type of research used evaluative. This study purposed to determine the effectiveness, adequacy, equity and accuracy in the evaluation of promotion policies. namely 1) effectiveness was still not in accordance with the policy because the promotion of positions carried out from the technical competence and managerial competence possessed by the promoted employee, 2) the adequacy was in accordance with the previous rank so that  they got promotion to their new position and also if seen from the years of service carried out the duties of the previous position, the average promoted employee had exceeded the policy provisions so that they could be promoted, 3) equal distribution was in accordance with applicable policies, both from ethnic groups from various regions, the implementation of promotions obtained by employees who had religion 4) accuracy, there were still many employees who were promoted due to lack of compensation, but some employees were already in accordance with the existing career path in the applicable policy. Keywords: Effectiveness, Adequacy, Equity, Accuracy, and Evaluation.